2017
DOI: 10.1177/0897190017712175
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Student-Led Ambulatory Medication Reconciliation Program at an Academic Institution

Abstract: Documentation from this innovative program suggests improvement in medication reconciliation and enhanced patient care with limited time required of student pharmacists. A similar program could be developed and utilized at other clinical sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 11 publications
2
8
0
Order By: Relevance
“…Student pharmacists' role in enhancing ambulatory care pharmacy practice Several studies have demonstrated the positive contribution of student pharmacists collecting medication histories, completing medication reconciliation, conducting patient interviews, performing point-of-care testing, and providing immunizations. [17][18][19][20][21][22][23] In an interprofessional setting, the use of fourth-year student pharmacists to obtain medication histories has been employed in a variety of clinics (e.g., internal medicine, cardiology, and pediatrics). 17 In this model, students spent an average of 10 minutes (range 2-30 minutes) collecting medication histories before reporting their findings back to the attending physician.…”
Section: Cppi Practice Forummentioning
confidence: 99%
See 4 more Smart Citations
“…Student pharmacists' role in enhancing ambulatory care pharmacy practice Several studies have demonstrated the positive contribution of student pharmacists collecting medication histories, completing medication reconciliation, conducting patient interviews, performing point-of-care testing, and providing immunizations. [17][18][19][20][21][22][23] In an interprofessional setting, the use of fourth-year student pharmacists to obtain medication histories has been employed in a variety of clinics (e.g., internal medicine, cardiology, and pediatrics). 17 In this model, students spent an average of 10 minutes (range 2-30 minutes) collecting medication histories before reporting their findings back to the attending physician.…”
Section: Cppi Practice Forummentioning
confidence: 99%
“…[17][18][19][20][21][22][23] In an interprofessional setting, the use of fourth-year student pharmacists to obtain medication histories has been employed in a variety of clinics (e.g., internal medicine, cardiology, and pediatrics). 17 In this model, students spent an average of 10 minutes (range 2-30 minutes) collecting medication histories before reporting their findings back to the attending physician. 17 Based on the time spent to obtain a full medication history, this model suggested that medical providers saved time by collaborating with student pharmacists, and students benefited by working in an interprofessional, real-word setting.…”
Section: Cppi Practice Forummentioning
confidence: 99%
See 3 more Smart Citations